PERCENTAGE OF HOT MIX ASPHALT MODIFICATION WITH HDPE POLYMER AND SYNTHETIC RUBBER COMPOSITE COMPOSITION BASED ON MARSHALL IDENTIFICATION AND COMPRESSIVE TEST - Junus, Stella; Renreng, Ilyas; Pratikto, Pratikto (Jurnal Rekayasa Mesin, 2025)
Hot Mix Asphalt is a combination of natural material composition with asphalt in the needs of highway infrastructure that is much needed. This study aims to identify the parameters of asphalt mixtures combined with HDPE type polymers and synthetic rubber in weight percentages of 4%, 5%, and 6% at temperature variations of 1700oC, 2000oC, and 2300oC which include density, Void Filled with Aspalt (VMA), Void in the mix (VIM), Void filled of Bitumen (VFB), Flow and Stability using Marshall tools, with the determination and orientation of loading carried out through a free pressure system or by Compressive Test to determine the fatique value in the loading process carried out. The optimum mixture rate is 5% with a temperature of 2000oC for HDPE type polymers, a mixture of 4% with a temperature of 2000oC for synthetic rubber mixtures, then for mixing both types of fillers the optimum mixing temperature is 1750oC, while the maximum loading value is located at 800 kN / cm2, the average load that can be received is 60 kN/s with cylindrical specimens with a height of 7 cm with a diameter of 10.5 cm.